Development of Doratoon-Based Video Animations Material of Algebra - Khofifatul, Khusna; Ikashaum, Fertilia (STKIP Singkawang, 2024)
This research aims to produce Doratoon-based animated math learning videos that are deemed feasible and practical for algebra material. This study is classified as development research or qualitative descriptive analysis. The development research is designed using the Hannafin and Peck development model, which includes the stages of needs analysis, design analysis, development analysis, and implementation. The results of this research show that the media experts obtained an average percentage score of 82%, indicating